(untitled) (Research, Society and Development, 2020)
The study aimed to evaluate the influence of slow pasteurization of juá pulp on its total phenolic compounds and its antioxidant activity. The fruits were manually harvested from juazeiro trees located in Limoeiro do Norte, Ceará. The pulp was obtained by homogenizing the fruits, without the seeds, and then it was placed in a glass container, where it was pasteurized at 65 °C for 30 minutes. The total extractable polyphenols (PET) was quantified and the antioxidant activity was determined by three different methods - Ferric reducing antioxidant power (FRAP) (μM Fe2SO4/g), ABTS•+ free radical scavenging activity (μM Trolox/g) and DHHP radical scavenging capacity (g/g DPPH). The juá in natura pulp had total extractable polyphenol content of 101.95 ± 6.58 mg/100 g and antioxidant activity of 36.33 ± 0.28 μM Fe2SO4/g; 35.33 ± 10.69 μM of Trolox/g; and 33.23 ± 7.29 g/g DPPH. After the thermal process, the PET concentration (129.79 ± 7.13 mg/100 g) and the antioxidant activity by the DPPH method (27.94 ± 13.84 g/g DPPH) increased without statistical difference (p ≥ 0.05), while using the ABTS (10.83 ± 2.41μM of Trolox/g) and the FRAP (24.30 ± 1.86 μM Fe2SO4/g) methods, a reduction was observed, with significant difference (p < 0.05) only for FRAP. The slow pasteurization (65 °C/30 min.) did not cause a significant reduction neither in the phenolic compounds nor in the antioxidant activity of juá pulp, indicating that it is an efficient process in terms of maintenance of its functional compounds.